A Prevalence Risk Analysis of Waterborne Transmission of SARS-CoV-2 - Abdullah R. Alanzi; Mohammad A. Parvez; Abdulrahman R. Alruwaili; Mohammad K. Parvez (Ital Publication, 2022)
We statistically analyzed 31 published studies comprising 113 water samples collected from 17 countries for SARS-CoV-2 positivity. The pooled estimated prevalence of viral RNA in the tested samples was 64.1% [95% CI:51.6%, 74.9%] with considerable heterogeneity (I2: 90.1%, P<0.001). Notably, wastewater, sewage, hospital septic-tank, biological sludge, and effluent demonstrated statistical significance (P<0.05) for RNA positivity. The country-wise pooled estimated prevalence for Germany, India, Turkey, Spain, the Netherlands, Italy, the USA, and Japan were 88% (76%, 94%), 85% (33%, 98%), 83% (43%, 97%), 78% (54%, 92%), 60% (41%, 77%), 53% (36%, 70%), 53% (27%, 77%), and 25% (13%,43%), respectively. Further subgroup analyses showed that the prevalence of SARS-CoV-2 among the tested water samples was significantly higher in middle-income countries compared to high-income groups. Our data, therefore, suggests wastewater-based epidemiological surveillance as an important tool for community-wide monitoring of SARS-CoV-2.   Doi: 10.28991/SciMedJ-2022-04-03-02 Full Text: PDF